2019
DOI: 10.1101/861203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase separation of Ede1 promotes the initiation of endocytic events

Abstract: Clathrin-mediated endocytosis is a major pathway that eukaryotic cells use to produce transport vesicles from the plasma membrane. The assembly of the endocytic coat is initiated by a dynamic network of weakly interacting proteins, but the exact mechanism of initiation is unknown. Ede1, the yeast homologue of mammalian Eps15, is one of the early-arriving endocytic proteins and a key initiation factor. In the absence of Ede1, most other early endocytic proteins lose their punctate localization and the frequency… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…These results agree with the apparent requirement for both Fcho1 and Eps15 to drive efficient endocytosis 3,6 . Notably, recent work by Kozak and Kaksonen 44 showed that the Saccharomyces cerevisiae homolog of Eps15, Ede1, can also form phase separated condensates in yeast cells, in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with the apparent requirement for both Fcho1 and Eps15 to drive efficient endocytosis 3,6 . Notably, recent work by Kozak and Kaksonen 44 showed that the Saccharomyces cerevisiae homolog of Eps15, Ede1, can also form phase separated condensates in yeast cells, in agreement with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, these data suggest that END sites are dynamic compartments containing an ensemble of endocytic proteins exhibiting hallmarks of LLPS. Notably, this conclusion is corroborated by a study posted on bioRxiv during the course of our manuscript preparation (Kozak and Kaksonen, 2019).…”
Section: Ends Exhibit Hallmarks Of Llpssupporting
confidence: 74%
“…In case of endocytosis, it has been suggested that LLPS of endocytic proteins serves as a principal mechanism by which the complex assembly of CME proteins during endocytosis is achieved (Bergeron-Sandoval et al, 2018;Day et al, 2019;Kozak and Kaksonen, 2019). What restricts liquid-liquid phase separation of CME proteins during regular endocytosis and inhibits END formation?…”
Section: Discussionmentioning
confidence: 99%
“…A liquid phase of proteins is generated through weak hydrophobic interactions. Previous studies demonstrate that 1,6-hexanediol, an aliphatic alcohol, can disrupt such interactions and dissolve a variety of liquid droplets including stress granules, P bodies, and endocytic proteins (Gopal et al, 2017;Kroschwald et al, 2015;Patel et al, 2007;Kozak and Kaksonen, 2019;Wilfling et al, 2020).…”
Section: Dyn1xa Puncta Are Phase-separatedmentioning
confidence: 99%